A Cognitive Perspective on the Arabic Spatial Noun فوق /Fawqa /Applying the Principle Polysemy Model - Mardiah, Zaqiatul; Wastono, Afdol Tharik; Muta’ali, Abdul (Paradigma: Jurnal Kajian Budaya, 2019)
The present paper provides a cognitive linguistics (CL) framework for analyzing the semantic structure of Arabic spatial noun fawqa based on Principled Polysemy Model (PPM) of Tyler and Evans (2003). PPM approach can broaden the narrow view of classical cognitive linguists regarding the semantic variation in the concept of physical- geometry of a preposition. As a polysemous lexeme, fawqa used by Arabian native to express a broad range of meanings, not only spatial relation but also non-spatial relation. The substantial sense of the lexeme is investigated using a large amount of corpus data (corpus.kacst.edu.sa) and applying the five steps of PPM approach. Through this approach, we ascertain that every single usage of fawqa expressing extended senses is always in its semantic network. Our study reveals that the usages of this lexeme in many situations and many cases show non-up down spatial relation, and non-physical relation, but they essentially refer to the primary sense.